2014
DOI: 10.1007/s00702-014-1276-1
|View full text |Cite
|
Sign up to set email alerts
|

Time- and frequency-domain parameters of heart rate variability and sympathetic skin response in Parkinson’s disease

Abstract: The autonomic nervous system (ANS) is regularly affected in Parkinson's disease (PD). Information on autonomic dysfunction can be derived from e.g. altered heart rate variability (HRV) and sympathetic skin response (SSR). Such parameters can be quantified easily and measured repeatedly which might be helpful for evaluating disease progression and therapeutic outcome. In this 2-center study, HRV and SSR of 45 PD patients and 26 controls were recorded. HRV was measured during supine metronomic breathing and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…There is ample evidence that cardiac autonomic dysfunction is an early finding in patients with LBD such as PD and DLB [15]. Several recent studies have found that HRV is more profound in patients with PD than in controls [15,16]; however, most of the PD patients enrolled had advanced stage disease and were taking medication (mean disease duration > 3…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There is ample evidence that cardiac autonomic dysfunction is an early finding in patients with LBD such as PD and DLB [15]. Several recent studies have found that HRV is more profound in patients with PD than in controls [15,16]; however, most of the PD patients enrolled had advanced stage disease and were taking medication (mean disease duration > 3…”
Section: Discussionmentioning
confidence: 98%
“…Several recent studies have found that HRV is more profound in patients with PD than in controls [15,16]; however, most of the PD patients enrolled had advanced stage disease and were taking medication (mean disease duration > 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the NMS, autonomic cardiovascular disorders have been associated with significant morbidity and mortality and with variable manifestations in patients affected by PD (Goldstein 2003), although the definite correlations with different subtypes of PD are not clear. In this context, analysis of heart rate variability (HRV) represents a not invasive and established tool in assessing cardiovascular autonomic modulation in different extrapyramidal disorders, especially in PD patients (Friedrich et al 2008;Valappil et al 2010;Maetzler et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The wave is considered to originate from sweat glands’ synchronized activation in response to discharges by efferent sympathetic nerve fibers. Though 1 study found SSR responses were not elicited only in a minority of individuals, and without related difference between PD patients and controls, [18] another study found that the SSR might provide valuable information on cholinergic sympathetic function in patients with PD. [19] In our study, we found that there was significant difference between PD and control groups in terms of the SSR ( P  < 0.01), significant prolonged SSR latencies and decreased SSR amplitudes from bilateral hands and both feet, and the absent lower limb SSR was determined in advanced PD patients.…”
Section: Discussionmentioning
confidence: 99%